THE DEVELOPMENT OF PROSUMPTION ON THE POLISH E-SERVICES MARKET (Polityki Europejskie, Finanse i Marketing)
In the information age, the growth of prosumer behavior would not be possible without the development of ICT technologies. The interactivity of contemporary media creates favourable conditions for the development of prosumption (a combination of “production” and “consumption.”) The article presents the problem of the behaviors of e-service consumers and demonstrates the results of a qualitative study which was conducted in 2018. For the purpose of the study, non-participant observation was adopted: conversations on internet forums dedicated to e-services were followed.